2012
DOI: 10.1002/biot.201100455
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety evaluation of recombinant protein production in goat mammary gland using adenoviral vectors: Preliminary study

Abstract: The production of recombinant proteins in the milk of non-transgenic goats can be achieved by transducing the mammary gland with recombinant adenoviral vectors. However, this process involves several regulatory issues. The current study evaluates the biosafety of this production system. We present a preliminary biosafety profile based on detection of adenoviral particles in different body fluids and the antibody response after adenoviral transduction of the goat mammary gland. In addition, two methods of adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The combination of methylene blue and white light irradiation effectively inactivated the Ad-E2 vector initially present in the first samples of milk collected. With this approach, the use of inactivating agents such as the potentially toxic beta-propiolactone was avoided, in contrast with other procedures previously proposed (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of methylene blue and white light irradiation effectively inactivated the Ad-E2 vector initially present in the first samples of milk collected. With this approach, the use of inactivating agents such as the potentially toxic beta-propiolactone was avoided, in contrast with other procedures previously proposed (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…54,84,85 The dAd5GNE vaccine is comprised of the GNE hapten (Figure 3) covalently linked to the proteins of a serotype 5 adenovirus (Ad5) disrupted to expose additional sites for GNE conjugation and co-administered with Adjuplex, a biodegradable matrix of carbomer homopolymer (cross-linked polyacrylic acids) and nanoliposomes derived from purified soy lecithin. The adenovirus has a favorable safety profile, demonstrated in clinical studies, 86 and was shown to stimulate a strong immune response when covalently conjugated to the cocaine analogue. 54,85 Pre-clinical assessment of the dAd5GNE vaccine demonstrated high titers of anti-GNE antibodies which blocked cocaine from reaching the central nervous system of mice, rats, and nonhuman primates.…”
Section: Clinical Advances In Anti-cocainementioning
confidence: 99%
“… 7 Therefore, adenovirus is frequently used for the gene therapy-based clinical trials to treat several diseases, such as cancers, cardiovascular diseases, central nervous system diseases, infectious diseases, etc. 8 , 9 , 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%